Analisis Pengaruh Electronic Word of Mouth melalui Instagram terhadap Brand Image dan Purchase Intention : Analisis Pengaruh Electronic Word of Mouth melalui Instagram terhadap Brand Image dan Purchase Intention - Bianka Andriyani; Ni Made Fitriani; Conny Tjandra Rahardja (Universitas Slamet Riyadi, 2022)
The purpose of this research is to analysis electronic word of mouth that affect brand image and purchase intention and brand image variabel that affect to purchase intention at Karsa Moyang. Sample of this research consist active Instagram users and followers Karsamoyang brand and there were 84 samples used. The data that was used in this research was primary data and selected by using purposive sampling method. The analytical method used is SEM Warppls by performing value calculation goodness of fit (inner model) and hypothesis test. Based on analytical result shows that electronic word of mouth affect brand image positively and significant. Electronic word of mouth variable affect purchase intention positively and significant. Brand image variable affect purchase intention positively and significant. Keywords: electronic word of mouth, brand image, purchase intention.